Thoughts on Labor Education Courses for Finance Majors in Applied Undergraduate Universities under the OBE Concept - Li, Yang (International Journal of Global Economics and Management, 2024)
Labor education is an important means of cultivating students' comprehensive and balanced development. The Ministry of Education emphasizes the strengthening of labor education for primary, secondary and college students, which reflects that education is not only about imparting knowledge, but also a process of shaping personality and cultivating abilities. Therefore, applied undergraduate colleges and universities as institutions that cultivate applied talents, should place greater emphasis on labor education. The article explores the problems that exist within the implementation of labor education courses for finance majors in applied undergraduate universities, and attempts to seek solutions for improvement based on the development laws of the financial industry.